An efficient iodine–DMSO catalyzed synthesis of quinoxaline derivatives. Issue 12 (25th March 2015) - Xie, Caixia; Zhang, Zeyuan; Yang, Bingchuan; Song, Gaolei; Gao, He; Wen, Leilin; Ma, Chen
Abstract: An efficient iodine–DMSO catalyzed system for the synthesis of quinoxaline derivatives was developed. The construction of this quinoxaline system went through a one-pot oxidation/cyclization process. The reaction afforded a variety of products in good to excellent yields. This methodology has potential applications in the synthesis of biologically and medicinally relevant compounds. Graphical abstract: